Crystal structure of 2,2′-bis[(2-chlorobenzyl)oxy]-1,1′-binaphthalene - Raja, Rajamani (Acta Crystallogr E Crystallogr Commun, 2015)
In the title binaphthyl compound, C(34)H(24)Cl(2)O(2), the dihedral angle between the two naphthyl ring systems (r.m.s. deviations = 0.016 and 0.035 Å) is 76.33 (8)°. The chlorophenyl rings make dihedral angles of 58.15 (12) and 76.21 (13)° with the naphthyl ring to which they are linked. The dihedral angle between the planes of the two chlorophenyl rings is 27.66 (16)°. In the crystal, C—H⋯O hydrogen bonds link molecules into chains propagating along [1-10]. The chains are linked by C—H⋯π interactions, forming a three-dimensional framework.